S 308 and other X-ray emitting bubbles around Wolf-Rayet stars - Camilloni, Francesco; Becker, Werner; Sasaki, Manami (Astronomy & Astrophysics, 2024)
Context. S 308 is an X-ray emitting bubble that surrounds the Wolf-Rayet star WR6. The structure shines in the optical as well and is thus known as the Dolphin Nebula. Due to its large angular extent, it has been covered at only 90% with past XMM-Newton observations. Aims. Thanks to the unique dataset provided by the all-sky survey performed in X-rays by SRG/eROSITA, we can show for the first time the image of the bubble in its entire extent in this band, together with its spectral characterization. Moreover, we have tried to apply the same procedure for other wind-blown bubbles detected in the optical/IR and we searched for X-ray extended emission around them. Methods. We first analyzed the diffuse emission of S308, providing a detailed spectral analysis. We then considered a sample of 22 optical/IR selected wind-blown bubbles from a previous study based on WISE data, providing an estimate of the X-ray flux for the first time. Results. We obtained the best fit for S308 with a two-temperature non-equilibrium plasma model (kT1 = 0.8-0.3+0.8 keV and kT2 = 2-1+3 keV) showing super-solar N abundance and low absorption. We did not detect any of the 22 optical/IR emitting bubbles in X-rays, but using our best fit model, we estimated the 3σ flux upper limits for each bubble. Conclusions. We demonstrate the new possibility offered by SRG/eROSITA to study known wind-blown bubbles and look for other ones. A two-temperature plasma description seems to fit the data quite well for S308. Since all of the 22 bubbles studied still remain undetected by SRG/eROSITA, it is very likely that absorption effects and spatial compactness are responsible for the challenges standing in the way of detecting these bubbles in soft X-rays.
CRIS-Team Scopus Importer:2024-02-16
Keywords: ISM: bubbles; stars: Wolf-Rayet; X-rays: general; X-rays: ISM